Model Penerapan Syariah dalam Negara Modern (Studi Kasus Arab Saudi, Iran, Turki, dan Indonesia) - Fauzan, Pepen Irpan; Fata, Ahmad Khoirul (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
Modernization of politics in islamic world causes hard dynamics in the relation betwen religion (sharī’ah) with state or politics. This paper tries to discuss the historical background of that discussion, and tries to show the models of sharī ’ah implementation in the context of modern state. The result of this study is that there are three models of sharī ’ah implementation in modern Islamic world: integration betwen religion (Islam) and state as in Saudi Arabia and Islamic Republic of Iran. In this model sharī ah formally becomes the positive law. The second model is secular state. In this model religion (and sharī’ah) separated from the state. The best example for this model is Republic of Turkey. And the last is symbiosis-intersectional model as Republic of Indonesia. This model is the middle position betwen both of them. The difference of the models are caused by the diversity of socio-historical-economic-political background of these states.